Evaluation of Caponization on Growth and Meat Quality Parameters of Dual-Purpose Chicken - Paudel, Tulasi Prasad; Poudel, Bishwas; Neupane, Damodar (International Journal of Applied Sciences and Biotechnology, 2018)
Caponization is a surgical technique that alters the sexual maturation of male chickens and improves quality characteristics of carcass and meat. The present experiment was conducted in order to evaluate the effects of caponization on body weight, carcass composition and meat quality of dual purpose chicken. A total of 48 dual-purpose breeds of Chicken, namely New Hampshire (NH) and Black Australorp (BA) were examined in a 2 × 2 factorial design each treatment having twelve birds till the age of 32 weeks. The results showed that the growth rate up until the age of 20 are not significant statistically which became significant afterwards (p